2012
DOI: 10.1177/0047287511434115
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate Exponential Smoothing for Forecasting Tourist Arrivals

Abstract: In this article, we propose a new set of multivariate stochastic models that capture time-varying seasonality within the vector innovations structural time-series (VISTS) framework. These models encapsulate exponential smoothing methods in a multivariate setting. The models considered are the local level, local trend, and damped trend VISTS models with an additive multivariate seasonal component. We evaluate the forecasting accuracy of these models against the forecasting accuracy of univariate alternatives us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 36 publications
1
41
0
Order By: Relevance
“…For example, Athanasopoulos and Silva (2012) developed a new set of forecasting models dealing with local level and trend, and damped trend with an additive multivariate seasonal components to forecast the demand for tourism. Another example is Shahrabi et al (2013) who proposed a modular genetic-fuzzy forecasting system by combining genetic fuzzy expert and data preprocessing systems.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…For example, Athanasopoulos and Silva (2012) developed a new set of forecasting models dealing with local level and trend, and damped trend with an additive multivariate seasonal components to forecast the demand for tourism. Another example is Shahrabi et al (2013) who proposed a modular genetic-fuzzy forecasting system by combining genetic fuzzy expert and data preprocessing systems.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…Multivariate approaches to tourist demand forecasting are few and have yielded mixed results. Athanasopoulos and Silva (2012) compared the forecasting accuracy of exponential smoothing methods in a multivariate setting against univariate alternatives. They used international tourist arrivals to Australia and New Zealand and found that multivariate models improved on forecast accuracy over the univariate alternatives.…”
Section: Design Of the Experimentsmentioning
confidence: 99%
“…While Athanasopoulos and Silva (2012) find that exponential smoothing methods in a multivariate setting improve the forecasting accuracy of univariate alternatives, du Preez and Witt (2003) obtain evidence that multivariate time series models do not generate more accurate forecasts than univariate time series models. When comparing the performance of different ANN models we are evaluating the impact of alternative ways of processing data on forecast accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…Most research efforts apply econometric models such as static almost-ideal demand system (AIDS) models (Han et al, 2006), error correction (EC) and co-integration (CI) models (Veloce, 2004;Ouerfelli, 2008, Lee, 2011, vector autoregressive (VAR) models (Song and Witt, 2006), time varying parameter (TVP) models (Song et al, 2011). Choice models (Talluri and van Ryzin, 2004) have also been increasingly used in revenue management.Time series models such as exponential smoothing (Athanasopoulos et al, 2012) and autoregressive integrated moving average (ARIMA) models (Claveria and Datzira, 2010;Assaf et al, 2011;Gounopoulos et al, 2012) have been widely used in the literature. While there is no consensus on the most appropriate approach to forecast tourism demand (Kim and Schwartz, 2013), there seems to be unanimity on the importance of applying new approaches to tourism demand forecasting (Song and Li, 2008), and on the fact that nonlinear methods outperform linear methods in modelling economic behaviour (Cang, 2013).…”
mentioning
confidence: 99%